The sequence and thresholds of leaf hydraulic traits underlying grapevine varietal differences in drought tolerance. (11th April 2020) - Dayer, Silvina; Herrera, José Carlos; Dai, Zhanwu; Burlett, Régis; Lamarque, Laurent J; Delzon, Sylvain; Bortolami, Giovanni; Cochard, Hervé; Gambetta, Gregory A
Abstract: Adapting agriculture to climate change is driving the need for the selection and breeding of drought-tolerant crops. The aim of this study was to identify key drought tolerance traits and determine the sequence of their water potential thresholds across three grapevine cultivars with contrasting water use behaviors, Grenache, Syrah, and Semillon. We quantified differences in water use between cultivars and combined this with the determination of other leaf-level traits (e.g. leaf turgor loss point, π TLP ), leaf vulnerability to embolism (P50 ), and the hydraulic safety margin (HSM P50 ). Semillon exhibited the highest maximum transpiration ( E max ), and lowest sensitivity of canopy stomatal conductance ( G c ) to vapor pressure deficit (VPD), followed by Syrah and Grenache. Increasing E max was correlated with more negative water potential at which stomata close (P gs 90 ), π TLP, and P50, suggesting that increasing water use is associated with hydraulic traits allowing gas exchange under more negative water potentials. Nevertheless, all the cultivars closed their stomata prior to leaf embolism formation. Modeling simulations demonstrated that despite a narrower HSM, Grenache takes longer to reach thresholds of hydraulic failure due to its conservative water use. This study demonstrates that the relationships between leaf hydraulic traits are complex and interactive, stressing the importance of integrating multiple traits in characterizing drought tolerance. Abstract : The relationships between traits including stomatal regulation, leaf embolism thresholds, and survival time under drought are complex and interactive, stressing the importance of integrating multiple traits in characterizing drought tolerance.